Utilization of User Generated Content (UGC)-Based Online Media by Citizen Journalists as a Development Communication Channel - Madonna, Metha; Siregar, Nasaruddin; Soelistyowati, Rr Dinar; Reza, Fikri; Neesha, Azzuri Raja (Journal of Science and Science Education, 2025)
Advances in Digital Communication Technology have significantly altered the landscape of journalism and broadcast media. Traditional boundaries of journalistic practice, once confined to established press institutions and public broadcasting, have expanded to include anyone, anywhere, anytime, through the phenomenon of citizen journalism. Originally emerging through social media, this form of journalism has been adopted by numerous online mass media via the User Generated Content (UGC) concept. While UGC has led to an overflow of information, it also offers opportunities for community-oriented individuals to disseminate information and socialize programs aimed at community empowerment. This paper proposes a detailed exploration into using UGC as a participatory extension channel to empower communities in their developmental efforts. The primary objective of this study is to design a framework for participatory extension using internet channels, enhancing the effectiveness of UGC in community development. This study adopts a qualitative research approach utilizing a phenomenological method to instrumentally describe observed phenomena and explore the expansive and beneficial potential of UGC media in development communication. The results of the study show that: (1) Citizen Journalism as a Participatory Tool: Citizen journalists represent a sector of the populace capable of actively participating in the communication of developmental processes and outcomes. This is primarily conducted through article uploads on UGC-based online media platforms. (2) UGC as an Alternative Communication Channel: UGC provides a low-cost, alternative channel for the dissemination of information and the socialization of development initiatives. Its potential to reach a broad audience makes it a valuable tool in development communication strategies